2020
DOI: 10.1111/1440-1681.13448
|View full text |Cite
|
Sign up to set email alerts
|

Gastric motor dysfunction coincides with the onset of obesity in rats fed with high‐fat diet

Abstract: Exposure to a high‐fat diet (HFD) has been reported to impair central autonomic and enteric neurocircuitries, however, the relevant mechanisms and their time course are inadequately clarified. This study aimed to investigate the effects of HFD consumption through the period of adolescence on gastric motor functions in adulthood. Male Sprague‐Dawley rats consumed a regular diet or HFD (60% kcal by fat) from 4 to 12 weeks of age. Body weight and food intake were monitored weekly. In adult rats, gastric emptying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The incidence rate of obesity keeps increasing for many years due to the improvement of living standards, excessive calorie intake and lack of physical exercise ( 28 ). High-fat diet is the direct cause of obesity ( 6 ). Extensive researches showed ANGPTL4 was an important regulator of TG metabolism by inhibiting LPL and pancreatic lipase ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of obesity keeps increasing for many years due to the improvement of living standards, excessive calorie intake and lack of physical exercise ( 28 ). High-fat diet is the direct cause of obesity ( 6 ). Extensive researches showed ANGPTL4 was an important regulator of TG metabolism by inhibiting LPL and pancreatic lipase ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences indicate that gut microbiota directly participates in obesity and many other metabolic diseases ( 4 , 5 ). A recent study have shown that obesity could be induced by the high-fat diet (HFD) ( 6 ). Meanwhile, the dysregulation in the composition and metabolic functions of gut microbiota would promote the development of obesity ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies in rats fed a high‐fat diet demonstrated that the increased visceral fat mass was linked with the development of a delayed gastric emptying, with attenuated bethanecol and sodium nitroprusside‐induced motor responses in antral and fundic isolated tissues. According to this model, gastric dysmotility linked with the over‐storage of visceral fat could depend on secondary alterations in the non‐adrenergic non‐cholinergic inhibitory neurotransmission 58 …”
Section: Discussionmentioning
confidence: 99%
“…According to this model, gastric dysmotility linked with the over-storage of visceral fat could depend on secondary alterations in the non-adrenergic non-cholinergic inhibitory neurotransmission. 58 Finally, an improvement of postprandial gastric emptying might also depend on varied levels of specific enterohormones affecting gastric motility. Glucagon-like peptide 1 (GLP-1) is secreted from the enterocytes following the luminal bile acid activation of the membrane receptor G protein-coupled receptor (GPBAR-1).…”
Section: Gastrointestinal Motility and Symptomsmentioning
confidence: 99%
“…In recent years, several reports have revealed that a correlation exists between NAFPD and MetS and suggest that it must be part of the definition of MetS[ 77 - 79 ]. Altered metabolism of fatty acids, induced by abdominal obesity, is a risk factor for cardiovascular disease and gastrointestinal disorders, including of the pancreas[ 80 , 81 ]. Whether the association of NAFPD and MetS is directly causal, or is a result of obesity, remains unclear and awaits further investigation.…”
Section: Clinical Consequences Of Nafpdmentioning
confidence: 99%